2019
DOI: 10.1108/wje-08-2018-0261
|View full text |Cite
|
Sign up to set email alerts
|

Field and numerical analysis on effect of axial load on the lateral response of a pile

Abstract: Purpose Piles often carry combination of axial and lateral. Currently, piles are designed separately for axial and lateral load. In the literature, few information is available on the influence of axial load on lateral behaviour of the pile. This paper aims to present the results of load deformation of a pile under pure lateral load and combined axial and lateral load. Design/methodology/approach The field load tests were carried out on four different pile diameters at two different bridge sites. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Theoretical research has indicated that the technical parameters of an interconnected fracture zone play a significant role in water-conservation coal mining (Jiao et al., 2018; Wang et al., 2017; Yin et al., 2019). In addition, various new techniques have been proposed for predicting the overburden failure zone, such as similar-material physical simulation and computer-based numerical simulation (Djamel et al., 2019; Huang and Wu, 2018; Yogendra and Gaurang, 2019), microseismic monitoring (Hill and Mauger, 2016; Tan et al., 2013; Yu et al., 2017), electromagnetic wave and resistivity chromatography (Li et al., 2019; Onyebueke et al., 2018), and the key stratum theory (Hu et al., 2019; Ju and Xu, 2013; Wu et al., 2014). All these methods have been analyzed qualitatively or quantitatively based on the simulation data and in-situ studies (Du and Gao, 2017; Guo et al., 2012; Liu et al., 2015; Miao et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical research has indicated that the technical parameters of an interconnected fracture zone play a significant role in water-conservation coal mining (Jiao et al., 2018; Wang et al., 2017; Yin et al., 2019). In addition, various new techniques have been proposed for predicting the overburden failure zone, such as similar-material physical simulation and computer-based numerical simulation (Djamel et al., 2019; Huang and Wu, 2018; Yogendra and Gaurang, 2019), microseismic monitoring (Hill and Mauger, 2016; Tan et al., 2013; Yu et al., 2017), electromagnetic wave and resistivity chromatography (Li et al., 2019; Onyebueke et al., 2018), and the key stratum theory (Hu et al., 2019; Ju and Xu, 2013; Wu et al., 2014). All these methods have been analyzed qualitatively or quantitatively based on the simulation data and in-situ studies (Du and Gao, 2017; Guo et al., 2012; Liu et al., 2015; Miao et al., 2011).…”
Section: Introductionmentioning
confidence: 99%